Impact of Lesion Preparation Technique on Side Branch Compromise in Calcified Coronary Bifurcations: A Subgroup Analysis of the PREPARE-CALC Trial. (11th November 2020) - Allali, Abdelhakim; Abdel-Wahab, Mohamed; Traboulsi, Hussein; Hemetsberger, Rayyan; Mankerious, Nader; Byrne, Robert; Geist, Volker; El-Mawardy, Mohamed; Sulimov, Dmitriy; Toelg, Ralph; Richardt, Gert
Abstract : Objectives . To analyze the impact of different techniques of lesion preparation of severely calcified coronary bifurcation lesions. Background . The impact of different techniques of lesion preparation of severely calcified coronary bifurcation lesions is poorly investigated. Methods . We performed an as-treated analysis on 47 calcified bifurcation lesions treated with scoring/cutting balloons (SCB) and 68 lesions treated with rotational atherectomy (RA) in the PREPARE-CALC trial. Compromised side branch (SB) as assessed in the final angiogram was the primary outcome measure and was defined as any significant stenosis, dissection, or thrombolysis in myocardial infarction flow <3. Results . True bifurcation lesions were present in 49% vs. 43% of cases in the SCB and RA groups, respectively. After stent implantation, SB balloon dilatation was necessary in around one-third of cases (36% vs. 38%; p = 0.82 ), and a two-stent technique was performed in 21.3% vs. 25% (p = 0.75 ). At the end of the procedure, the SB remained compromised in 15 lesions (32%) in the SCB group and 5 lesions (7%) in the RA group (p = 0.001 ). Large coronary dissections were more frequently observed in the SCB group (13% vs. 2%; p = 0.02 ). Postprocedural levels of cardiac biomarkers were significantly higher in patients with a compromised SB at the end of the procedure. Conclusions . In the PREPARE-CALC trial, side branch compromise was more frequently observed after lesion preparation with SCB as compared with RA. Consequently, in calcified bifurcation lesions, an upfront debulking with an RA-based strategy might optimize the result in the side branch.